دور ممارسة الأنشطة اللاصفية الكشفية على الصحة النفسية لتلاميذ مرحلة التعليم المتوسط دراسة ميدانية بمدينة الوادي(الجزائر) - محمدي, عبد الرحمان; غبريني, رشيد (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة إلى إبراز دور ممارسة الأنشطة اللاصفية الكشفية على الصحة النفسية لتلاميذ مرحلة التعليم المتوسط ببلدية الوادي، حيث إعتمد الباحثان على المنهج الوصفي السببي المقارن من خلال تطبيق مقياس الصحة النفسية من إعداد الباحثين على عينة تم اختيارها بطريقة قصدية تقدر 160 تلميذا ذكور (80 تلميذا ذكر ممارسين للأنشطة اللاصفية الكشفية و80 تلميذا ذكر غير ممارسين لأي نشاط لاصفي ) من متوسطات بلدية الوادي للموسم الدراسي 2018/2019 ، وبعد جمع البيانات وتحليلها إحصائيا ببرنامجspss؛ كشفت النتائج على وجود علاقة ارتباطيه بين ممارسة الأنشطة اللاصفية الكشفية والصحة النفسية لدى التلاميذ الكشافين، ووجود فروق ذات دلالة إحصائية بين التلاميذ الممارسين للانشطة اللاصفية الكشفية وغير الممارسين على مقياس الصحة النفسية لصالح التلاميذ الممارسين.The study aimed to highlight the role of scouting extra-curricular activities on the mental health of middle school students in the municipality of El-oued, Where the researchers relied on the comparative descriptive causal approach through the application of the mental health scale prepared by the researcher on a sample chosen intentionally, estimated at 160 male students (80 male practicing students). Scout extracurricular activities and 80 male students not practicing any extracurricular activity) from the averages of El-oued Municipality for the 2018/2019 academic season, and after data collection and statistical analysis using the spss program; The results revealed that there is a correlation between the practice of Scout extra-curricular activities and the mental health of the Scouts students, and the presence of statistically significant differences between the practicing pupils of Scout extra-curricular .activities and the non-practicing students in the mental health scale in favor of the practicing students.
The role of scouting extracurricular activities on the mental health of middle school students A field study in El-Oued city (Algeria)
مقال
Keywords: اللأنشطة اللاصفية الكشفية، الحركة الكشفية، الصحة النفسية، مرحلة التعليم المتوسط.; Mental Health, Scout extra-curricular , activitiesscouting movement , middle school stage.